Once upon a deadpool [videorecording (Blu-Ray)] - Reynolds, Ryan; Reynolds, Ryan; Brolin, Josh; Baccarin, Morena; Savage, Fred, 1976- (Twentieth Century Fox Home Entertainment, 2018)
A Deadpool fairy tale that gives zero F's.